2022
DOI: 10.3389/fmicb.2022.821679
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and Salinity on the Ability of Salmonella Serotypes to Form Biofilm

Abstract: Salmonella is a major cause of food-borne infections in Europe, and the majority of human infections are caused by only a few serotypes, among them are Salmonella enterica subsp. enterica serotype Enteritidis (hereafter Salmonella Enteritidis), Salmonella Typhimurium, and the monophasic variant of S. Typhimurium. The reason for this is not fully understood, but could include virulence factors as well as increased ability to transfer via the external environment. Formation of biofilm is considered an adaptation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…To describe the shedding of viral RNA in males and females and to monitor the hamsters’ weights during infection of males and females versus the corresponding group of mock animals, we performed a descriptive statistical analysis using SAS 9.4 software [ 62 , 63 , 64 ]. We applied a spline mixed model according to sex while taking into account the correlation between different observations of the same hamster over time using a first-order autoregressive (AR(1)) structure for the covariance matrix.…”
Section: Methodsmentioning
confidence: 99%
“…To describe the shedding of viral RNA in males and females and to monitor the hamsters’ weights during infection of males and females versus the corresponding group of mock animals, we performed a descriptive statistical analysis using SAS 9.4 software [ 62 , 63 , 64 ]. We applied a spline mixed model according to sex while taking into account the correlation between different observations of the same hamster over time using a first-order autoregressive (AR(1)) structure for the covariance matrix.…”
Section: Methodsmentioning
confidence: 99%
“…Eighty-seven S. enterica strains, belonging to the selection of isolates already described in Petrin et al (2022) , were included in this study. Briefly, the strains were isolated in Italy between 2009 and 2019 and belonged to the collection of the Italian National Reference Laboratory for Salmonellosis, Istituto Zooprofilattico Sperimentale delle Venezie (IZSVe) and the Istituto Superiore di Sanità (ISS).…”
Section: Methodsmentioning
confidence: 99%
“…This GLM parameterization was chosen given the positively skewed P(inf) distribution. The same approach was used to test associations between P(inf) and biofilm formation ability under different experimental conditions, as studied by Petrin et al (2022) . Estimates were thus adjusted for differences among serovars and sources of isolations (covariates), and clustering of observation (replicates) at the isolate level using cluster-robust (Sandwich) variance estimators ( Williams, 2000 ).…”
Section: Methodsmentioning
confidence: 99%
“…Changing from a planktonic state to a biofilm state confers various advantages to microorganisms, such as antimicrobial resistance, evasion of host immune response, resistance to oxidative stress, and compensation for lack of nutrients [26][27][28][29][30][31]. Several genetic studies have shown that the formation of biofilms depends on factors such as the mobility of microorganisms [31][32][33], the synthesis of exopolysaccharides [33][34][35], environmental conditions: temperature, pH, oxygen availability [36,37], and nutrient availability [38]. Several steps detail the process of biofilm formation.…”
Section: Biofilm Formationmentioning
confidence: 99%